Pengaruh Suhu Transesterifikasi Pada Pembuatan Bahan Baku Produk Biodiesel dari Biji Karet Menggunakan Katalis CaO/ ZnO/ y-Al2O3 - Putri; Ida Hasmita; Nadia Putri Mauliza; Zulhaini Sartika; Chairul Amni (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Rubber seed is a source of vegetable oil that can be used for biodiesel production, but its use is not optimal. Although rubber seeds contain a lot of oil, it is possible to process them into biodiesel and become a renewable energy source from vegetable oil. The aim of this research is to determine the maximum yield and the effect of temperature on the transesterification process. The results of the research show that temperature variations affect the properties of the obtained biodiesel, namely the maximum yield at a temperature of 60 ºC is 90%, the density value in accordance with SNI 7182:2015 at a temperature of 80 ºC is 853.5 kg/m3, the viscosity value in accordance with SNI 7182:2015 at a temperature of 60 ºC and 70 ºC with a value of 2.83 mm2/cSt and 2.19 mm2/cSt respectively. The GC-MS analysis was carried out on the best samples with density values according to SNI 7182:2015, namely samples with a temperature of 80ºC for 60 minutes and consisting of methyl ether linoleic acid with a surface area of 35.32% and oleic acid methyl ester with a surface area of 4.46%